2020
DOI: 10.4103/jips.jips_106_20
|View full text |Cite
|
Sign up to set email alerts
|

Propolis extract and bovine bone graft combination in the expression of VEGF and FGF2 on the preservation of post extraction socket

Abstract: Aim: To determine the potential of propolis extract and BBG combination on the quantity of fibroblast growth factor 2 (FGF-2), vascular endothelial growth factor (VEGF), and osteoblasts in the preservation of tooth extraction socket on days 3 and 7. Settings and Design: Laboratory in vivo reseach using animal model. Materials and Methods: Fifty-six Cavia cobaya were divided into eight groups containing seven animals in each group. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In two studies by Kresnoadi et al, male guinea pigs with OTM treated with propolis (2% propolis in polyethylene glycol; 0.1 mL propolis extract) for 3 and 7 days showed increased bone formation at the alveolar bone, as evidenced by increased osteoblast number and protein expression of osteocalcin. Propolis also reduced bone resorption at the alveolar bone, as evidenced by decreased osteoclast number [50,51]. In another study by Wiwekowati et al [52], propolis treatment (5% propolis gel for 17 days) showed increased osteoblast number in the alveolar bone of rats with OTM.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In two studies by Kresnoadi et al, male guinea pigs with OTM treated with propolis (2% propolis in polyethylene glycol; 0.1 mL propolis extract) for 3 and 7 days showed increased bone formation at the alveolar bone, as evidenced by increased osteoblast number and protein expression of osteocalcin. Propolis also reduced bone resorption at the alveolar bone, as evidenced by decreased osteoclast number [50,51]. In another study by Wiwekowati et al [52], propolis treatment (5% propolis gel for 17 days) showed increased osteoblast number in the alveolar bone of rats with OTM.…”
Section: Discussionmentioning
confidence: 91%
“…The bone healing properties of propolis were explored using critical non-union bone defects in Wistar rats (dose of propolis: 0.1 mL of 250 mg/mL propolis percutaneously with chitosan or bone graft) [44], femur fracture in Sprague Dawley rats (implanted with 60% propolis loaded implants and treated with 200 mg/kg of propolis) [45], distraction osteogenesis in New Zealand white rabbits (dose of propolis: 100 and 200 mg/kg) [46]. For the periodontal models, periodontitis-induced bone loss in Wistar rats and C57BL/6 mice (dose of propolis: 100-200 mg/kg) [47][48][49], orthodontic tooth movement (OTM) in Wistar rats and guinea pigs (dose of propolis: 2-5% and 100 µL of propolis) [50][51][52]; delayed tooth replantation in Wistar rats (dose of propolis: 200 mL of 15% propolis solution) [53], rapid maxillary expansion (RME) in Wistar rats (dose of propolis: 100 mg/kg or propolis) [54]; grade II furcation-induced bone loss in mongrel dogs (dose of propolis: 400 mg in graft) [55] were studied. In animal studies, densitometry method was used to measure bone mass, micro-computed tomography and bone histomorphometry were used to determine bone microstructure, and circulating bone markers were used to estimate the bone remodelling.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 male Cavia cobaya represented the subjects of this study being the number featured in Lemeshow’s formula according to a similar previous study conducted by Kresnoadi et al (2020) ( Kresnoadi et al, 2020a ). The subjects had to satisfy certain criteria, namely; healthy, 3–3.5 months old, 300–350 g in weight, lesion-free and with full command of the five senses.…”
Section: Methodsmentioning
confidence: 99%
“…This combination of material was needed in terms of socket preservation to maintain jaw bone volume after tooth extraction procedure. [ 14 ] At present, the potential for osteogenic formation resulting from a combination of ZOT rhizomes liquid extract remains unknown. The purpose of this study was to determine the expression of osteogenic in a combination of ZOT rhizome liquid extract in postextraction tooth sockets.…”
Section: Introductionmentioning
confidence: 99%